Born-Oppenheimer and Renner-Teller Quantum Dynamics of CH(X2?) + D(2S) Reactions on Three CHD Potential Surfaces - Gamallo, Pablo; Akpinar, Sinan; Defazio, Paolo; Petrongolo, Carlo (Amer Chemical Soc, 2015)
The quantum dynamics of three CH(X-2 Pi) + D(2S) reactions is studied by means of the coupled-channel time-dependent real-wavepacket (WP) and flux methods at collision energy E-colc <= 0.6 eV and on three potential energy surfaces (PESs): the BornOppenheimer (BO) ground PES X(3)A '' and the excited ones a(1)A' and b(1)A '', coupled by nonadiabatic (NA) RennerTeller (RT) effects. This three-state model is suitable for obtaining initial-state-resolved observables, is based on a complete analysis of the correlation diagram of the lowest electronic states of the CHD intermediate and of their NA interactions, and neglects the smaller coupling effects due to the asymptotic electronic angular momenta that become important in state-to-state dynamics. WPs are propagated on each PES at total angular momentum values J <= 70, with CH in the two lowest vibrational states v(0) and in the ground rotational state j(0) = 1. Reaction probabilities are obtained for three possible final products (f): (dP) CH decay and C(P-3) + HD(X-1 Sigma(+)) formation that occurs on the uncoupled ground PES, (dD) CH decay and C(1D) + HD(X-1 Sigma(+)) formation that depends on the RT-coupled singlet species, and (ex) exchange to CD(X-2 Pi) + H(2S) available adiabatically from the X(3)A '' PES and nonadiabatically from a(1)A' and b(1)A ''. Observable cross sections sigma(f,v0j0) and rate constants k(f,v0j0) in the temperature range T = 1002000 K are obtained for (dP), (dD), and (ex) channels. Comparing BO with RT probabilities, we show that NA effects are important at high J values for the (ex) channel at v0 = 1. Real time mechanisms on the three PESs show that RT couplings are opened after some time and clearly point out the formation of the product channels. Both cross sections and rate constants present the same sequence, for example sigma(ex,11) > sigma(dD,01) similar to sigma(ex,01) sigma(dD,11) sigma(dD,11) sigma(dD,01), and the CH vibrational excitation enhances the total removal CH+D reactivity by a factor of similar to 1.7, mainly due to the increase of the (ex) channel contribution from similar to 47% at v(0) = 0 to similar to 76% at v(0) = 1. This fact implies a considerable vibrational enhancement of combustion processes at high temperature. In agreement with the probability results, the a(1)A'/b(1)A '' RT coupling increases both sigma(ex,11) and k(ex,11) up to similar to 30%. Moreover, including the three PESs in the dynamics simulation of CH+D increase by far the (ex)/(dP) branching ratio with respect to the CH + H' reaction. Thus, at room temperature, k(dP,01) changes from 10.8 x 10(11) to 3.4 x 10(11) cm(3) s(1) substituting H atom by D.
Keywords: Molecular-Beam Experiments; Potential-Energy Surfaces; Scattering; Ch; C(D-1)+H-2; System; H-2